A Critical Listening Teaching Model with Students’ Self-Mediated Podcast to Enhance Critical Thinking: ARRRIPS Model - Arif Suryo Priyatmojo; Issy Yuliasri; Abdurachman Faridi; Charanjit Kaur Swaran Singh (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study addresses the challenge of fostering critical thinking in English as a Foreign Language (EFL) instruction, particularly in the Critical Listening course. To meet this need, the ARRRIPS model—Analyze, Review, Revise, Record, Immediately Podcast, and Share was developed. The research adopted a Research and Development (R&D) design guided by the ADDIE model. Conducted at Universitas Negeri Semarang (UNNES), the study involved two classes: an experimental group using the ARRRIPS model and a control group receiving a conventional instruction model. A quasi-experimental design was applied to evaluate the model’s effectiveness, using pre- and post-tests for quantitative analysis, and interviews, observations, and students’ artefacts for qualitative insights. Instruments included a validated critical thinking rubric based on Facione’s (1990) framework, perception questionnaires, interview guides, and observation checklists. Quantitative data analyzed with SPSS 25 showed a significant difference between the experimental group (mean = 15.59) and the control group (mean = 7.97; p < 0.001). Qualitative data revealed enhanced engagement, autonomy, and metacognitive reflection among the students. The study concludes that the ARRRIPS model effectively improves critical thinking in EFL listening instruction. It offers a practical, technology-integrated framework aligned with Merdeka Curriculum goals and learner-centered pedagogies.